Pengelolaan Pariwisata Berbasis Masyarakat (Community Based Tourism) Di Objek Wisata Tangkahan - Aina Rahmayani; Sabam Syahputra Manurung (Yayasan Literasi Sains Indonesia, 2022)
Community-based tourism is a concept that prioritizes the active participation of the community with the aim of providing welfare. Tangkahan Village, Langkat Regency is a cultural heritage that is a traditional tourist attraction that is crowded with tourists. However, in its development, there is an issue that tourism does not contribute to improving the quality of life of local residents. In this study, it will be studied on how tourists' opinions towards the community as tourism managers in Tangkahan tourist attractions and examine how the quality of community-based tourism management in Tangkahan Tourism Objects. This type of research is qualitative research, through a descriptive method, which will discuss the phenomenon of community-based tourism management in the Tangkahan Tourist Attraction area both from the perspective of tourists and from tourism managers. The theoretical basis of tourism management is used as a guide so that the research focus is in accordance with the facts in the field. The results of this study were 46.7% rated that the quality of service at Tangkahan tourist attractions was at good value, 56.7% rated that the condition of the facilities in Tangkahan tourist attractions was quite good, 46.7% rated that the tourist attractions provided by tangkahan tourist attraction managers were good. Then the reduction of tourists due to restrictions and prohibitions on tourists from visiting due to pandemic policies by the government